Ochre and biochar: technologies for phosphorus capture and re-use - Shepherd, Jessica Grace (The University of Edinburgh, 2017)
Despite recent instability in the global supply of phosphate-rock derived fertiliser and the potential for this to continue into the future, the recovery of phosphorus (P) from wastewater treatment systems, where P is abundant and accessible, is well below maximum potential. Considerable resource is spent on removing P from wastewater in order to comply with environmental standards and to protect aquatic ecosystems from eutrophication, yet there is little emphasis on capturing the P in a way that is optimised for re-using it as agricultural fertiliser. To address this lack of innovation in the face of climate change and food insecurity, a concept for a material capable of capturing P from wastewater was developed, with an emphasis on the utilisation of otherwise waste materials and the use of carbon neutral or negative production technologies. Based on the demonstrated P capture properties of coal minewater treatment waste (ochre) and biochar made from anaerobically digested feedstocks, a range of biochars were designed and produced using different mixtures of ochre (“OC”), sourced from the UK Coal Authority Minto minewater treatment scheme in Fife, Scotland and anaerobically digested sewage sludge (“AD”), sourced from the Newbridge wastewater treatment plant in Edinburgh. A first generation of materials consisting of either AD or a 1:1 mixture (dry weight basis) of OC and AD were produced in a small-scale batch pyrolysis unit at two pyrolysis highest treatment temperatures (HTTs) (450 and 550°C) to give the biochars AD450, AD550, OCAD450 and OCAD550. These were tested for their P capture properties in repeated P-exposure experiments with pH buffering in comparison to unpyrolysed ochre, activated carbon and a natural zeolite. After 5 days of repeated exposure to a P solution at a wastewater-relevant concentration (20 mg P l-1) replenished every 24 h, relatively high masses of P were recovered by ochre (1.73 ± 8.93×10-3 mg P g-1) and the biochars OCAD550 (1.26 ± 4.66×10-3 mg P g-1), OCAD450 (1.24 ± 2.10×10-3 mg P g-1), AD450 (1.06 ± 3.84×10-3 mg P g-1), and AD550 (0.986 ± 9.31×10-3 mg P g-1). The biochar materials had higher removal rates than both activated carbon (0.884 ± 1.69×10-2 mg P g-1) and zeolite (0.130 ± 1.05×10-2 mg P g-1). To assess the extractability of recovered P and thus potential plant bioavailability, P exposure was followed by repeated extraction of the materials for 4 days with pH 7-buffered deionised water. The AD biochars retained 55% of the P recovered, OCAD biochars 78% and ochre 100%. Assessment of potentially toxic element (PTE) concentrations in the biochars against guideline values indicated low risk associated with their use in the environment. A second generation of materials were produced to examine the scalability of the concept. Mixtures of AD and OC were pelletised with a lignin binder (89.1:9.9:1.0 ratio, dry weight basis) and AD was pelletised with binder (99:1 ratio, dry weight basis). The pelletised feedstocks were pyrolysed in a bench-scale continuous flow pyrolysis kiln at the same two HTTs to give the pelletised biochars PAD450, PAD550, POCAD450 and POCAD550. Analysis of digested biochar samples compared to the previous generation of biochars showed general similarities between the two groups, apart from the substantially lower Fe content. Sub-samples of the pelletised biochars were exposed to a 20 mg l-1 P solution over 6 days, with the solution replaced every 24 h to give the P-exposed biochars EPAD450, EPAD550, EPOCAD450 and EPOCAD550. To probe the mechanisms of P capture by these materials and how feedstock preparation and pyrolysis conditions affected these, spectroscopic analysis using laser-ablation (LA) ICP-MS, X-ray diffraction, X-ray photo-electron spectroscopy (XPS) and scanning electron microscopy coupled with energy dispersive X-ray was performed. The results highlighted the general importance of Fe minerals in P capture and subsidiary roles for Al, Ca and Si. A 3-week barley (Hordeum vulgare) seedling growth experiment was conducted using the pelletised and P-exposed biochars, in comparison with other biochars produced using feedstock which contained high amounts of PTEs. The biochars were also extracted using a range of different methods used to assess the bioavailability of PTEs and nutrients in soils, and the results compared to digests of barley leaves to identify whether any of these could reliably predict plant bioavailability in biochar. The above ground biomass and its total P concentration of barley grown in a 5% mixture of EPOCAD550 in sand was significantly higher than the control (p < 0.05 and p < 0.01, respectively). A significant positive correlation between mean leaf P mass and dry weight leaf yield (R2 = 0.865, p < 0.001) was found, indicating that dry weight yield could be used as an indicator for the P fertilising capability of biochar for barley seedlings. Element concentrations in unbuffered and buffered and (pH 7) 0.01 M CaCl2 biochar extractions were significantly positively correlated with plant leaf concentration for 6 of the 18 elements investigated, more than any of the other extractions. A longer barley growth experiment was conducted, using rhizoboxes, to test the bioavailability of P in the biochars compared to conventional fertiliser. The pelletised and Pexposed biochars were applied to a sandy loam soil with P constraints. Biochar application rates were based on 2% formic acid extractable P, calculated for summer barley using Index 0 soil. Analysis of total leaf length at harvest (12 weeks), dry weight yield, leaf P concentration and leaf P mass showed no significant differences between the biochar treatments, NPK fertilised and NK fertilised controls. This shows that biochar, when applied at low total application rates based on extractable P, is as effective as conventional fertiliser. Now that AD biochar materials have been shown to have useful phosphorus recycling properties in laboratory experiments, additional work is required to optimise their use in wastewater and agricultural systems. The next stage of research should determine their performance in flow-through filtration systems with simulated and real wastewater effluent, as well as their performance in field trials with different crops of interest to demonstrate their potential as viable alternative fertilisers.
Keywords: phosphorus recycling; biochar; agriculture; fertiliser; wastewater treatment